Saberes pedagógicos/comunicacionais, pesquisa/formação: reflexões sobre as experiências formativas das professoras online - Ferreira, Maria da Conceição Alves (2012)
The thesis, entitled, Pedagogical/comunication knowledge, research/formation: Reflections on the formative experiences of teachers online , developed dialogues on the pedagogical/communication knowledge, research-formation and the formative experiences of teachers online, for the purpose of understanding how pedagogical/communication knowledge is establishing/established from the formative experience of teachers online. For this reason we began with the following question: how does pedagogical/communication knowledge become estabilishing/established beginning with the formative experience of teachers online? The methodological approach for the selected research was research/formation, based on Ethnoresearch of critical formation. This became a rich route for reflections on pedagogical/communication knowledge and formative experiences, making a contribution for formation and autoformation of the teacher/researcher and the teachers online. This provided moments of formation, of reflection-in-action and on the action, potentialized/structured the process of comprehending, analyzing, interpreting, reflecting on the formative experiences and contributing for reflections on pedagogical/communication knowledge of the teacher online. The theoretical referential dialogue was based on concepts such as: education online, interactivity Silva (2002), Santos (2005), Moran (2003), teaching, Veiga (2005), Pimenta (2002), Freire (2005), Tardif (2002), teaching online Sacramento (2006), teaching knowledge Tardif (2002), Charlot (2000), Porlán (1997), García (1992), Freire (2005), Ethnoresearch-formation Macedo (2000), formation Macedo (2010), Josso (2010). The discoveries revealed that the pedagogical/communication knowledged becomes establishing/established beginning with formative experience of the teachers online, from the emergency of a collective communicative dialogue, structuring and potentialized by the experiences of the context online, from the didactic pedagogical/communicational organization online, of the research, of the relation created by the expertise and the presents itself along the itinerary of the family , the school, academic and professional. From this we can conclude that of knowledge and plural experiences, which became broken down because they are parts that relate themselves with other parts, which become united in one whole, the singular/plural, the local/global, the text and the context, agregating principles a pedagogical- communication perspective that orients :the dialogue, the interactivity, the hypertextuality, themultivocallity, formative dispositions, formative experiences all of wich makes for the possibilities for researdh and the training of professors and teachers who accept their point of departure and enddind points as pedagogy and experience